2012
DOI: 10.5051/jpis.2012.42.6.217
|View full text |Cite|
|
Sign up to set email alerts
|

Bacterial adhesion and colonization differences between zirconia and titanium implant abutments: an in vivo human study

Abstract: PurposeSeveral parameters have been described for determining the success or failure of dental implants. The surface properties of transgingival implant components have had a great impact on the long-term success of dental implants. The purpose of this study was to compare the tendency of two periodontal pathogens to adhere to and colonize zirconia abutments and titanium alloys both in hard surfaces and soft tissues.MethodsTwelve patients participated in this study. Three months after implant placement, the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…In contrast, a recent study showed zirconia abutments presented a smaller microgap . Also, no significant difference was observed between zirconia and titanium abutments in the amount of oral pathological bacteria, pro‐inflammatory cytokine, and bone metabolism mediator profiles …”
mentioning
confidence: 90%
See 1 more Smart Citation
“…In contrast, a recent study showed zirconia abutments presented a smaller microgap . Also, no significant difference was observed between zirconia and titanium abutments in the amount of oral pathological bacteria, pro‐inflammatory cytokine, and bone metabolism mediator profiles …”
mentioning
confidence: 90%
“…11 Also, no significant difference was observed between zirconia and titanium abutments in the amount of oral pathological bacteria, pro-inflammatory cytokine, and bone metabolism mediator profiles. 12,13 Moreover, zirconia abutments presented discrepant machinability in the clinical application. One of the most common complications of zirconia abutments is incidental fracture or chipping, which may be associated with several factors, including occlusal force distribution, the mechanical strength of abutment material, abutment design, and manufacturing process.…”
mentioning
confidence: 99%
“…The common esthetical impairments at the critical interface between the marginal gingiva and the prosthetic components (Ozkurt & Kazazoglu, 2011) may be avoided by using ceramic abutments and transgingival components for implant restorations (Hahnel, Rosentritt, Handel, & Burgers, 2009). Finally, the biocompatibility and reduced proneness of microorganisms to adhere (Hisbergues et al, 2009; Scarano, Piattelli, Caputi, Favero, & Piattelli, 2004) make zirconia a suitable dental implant material with clinical success rates almost comparable to titanium implants (Do Nascimento et al, 2013; Lee et al, 2011; de Oliveira et al, 2012; Rimondini, Cerroni, Carrassi, & Torricelli, 2002; Scarano et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…While much information is available on bacterial colonization of dental ceramic materials (Al‐Ahmad et al, 2010; van Brakel et al, 2011; Do Nascimento et al, 2013; Egawa, Miura, Kato, Saito, & Yoshinari, 2013; Hahnel et al, 2009; Lee et al, 2011; de Oliveira et al, 2012; Rosentritt et al, 2009; Sardin, Morrier, Benay, & Barsotti, 2004; Scotti et al, 2007; Viitaniemi, Abdulmajeed, Sulaiman, Soderling, & Narhi, 2017; Yamane et al, 2013), less is known about fungal adherence to zirconia surfaces (Burgers et al, 2010; Dal Piva et al, 2018; do Nascimento, Pita, Pedrazzi, de Albuquerque Junior, & Ribeiro, 2013; Ehrman et al, 2006; Li et al, 2012). This in vitro study intended to characterize the surface properties such as roughness and surface‐free energy of glazed and polished monolithic yttria‐stabilized zirconia (Y‐TZ P ) polycrystal ceramics and to evaluate the ability of C. albicans and salivary bacteria, Staphylococcus epidermidis, mixed with C. albicans , respectively, to adhere to these substrata.…”
Section: Introductionmentioning
confidence: 99%
“…Studies evaluating the internal colonization of implants applied cultivation (Persson et al 1996;van Winkelhoff et al 2000), scanning electron microscope equipped with energy dispersive X-ray spectrometer (Rimondini et al 2001), DNA probe analysis (Callan et al 2005), or DNA checkerboard hybridization (do Nascimento et al 2011). Real-time polymerase chain reaction (realtime PCR) was used for the evaluation of bacterial colonization of implant surfaces in humans (Th€ one-M€ uhling et al 2010;de Oliveira et al 2012). For the identification and quantification of periodontopathogenic bacteria, real-time PCR has been introduced and compared with cultivation (Jervøe-Storm et al 2005;Boutaga et al 2006;Verner et al 2006).…”
mentioning
confidence: 99%